Preliminary studies on the carcass characteristics of native breeds of woolless sheep in hot tropical semiarid Northeast Brazil - Figueiredo, E.A.P.; Simplício, A.A.; Riera, G.S.; Pant, K.P. (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out to evaluate the potentiality of meal production in male lambs of three indigenous breeds of hairy (woolless) sheep maintained on native "caatinga" pastures up to six or seven months of age, and, if necessary, under stall-feeding subsequently, in the hot tropical Northeast Brazil. The results showed that the optimum slaughter weight of 25 kg was reached in Santa Inês and some of the Morada Nova lambs on native pastures by the time they were six to seven months of age. Some other twin-born lambs of Morada Nova and all lambs of Brazilian Somali breeds did not reach the weight till seven months of age and these animals had to be stall-fed for additional period. These reached the optimum slaughter weight at around nine to ten months of age. Thus, Santa Inês breed had the best growth, Morada Nova was intermediate and Brazilian Somali had the minimum growth. These breed differences, which reflect their adult body sues, also influenced some of the carcass characteristics. The type of birth appeared to have a marked effect on size, growth and some of the carcass characteristics. Single-born lambs had a distinct advantage. There was virtually no difference in the carcass characteristics of older and younger lambs of comparable weights and it appeared that these traits were related more to the weight of lamb at slaughter.
Keywords: Santa Inês; Morada Nova; Brazilian Somali; meat productivity; native caatinga pastures; stall-feeding